Seizure-like behavior and hyperactivity in napb knockout zebrafish as a model for autism and epilepsy - Kyung Chul Shin (13913556) (2025)
We identified N-ethylmaleimide-sensitive factor attachment protein beta (NAPB) as a potential risk gene for autism and epilepsy. Notably, Qatari monozygotic triplets with loss of function mutations in NAPB exhibit early onset epileptic encephalopathy and varying degrees of autism. In this study, we generated NAPB zebrafish model using CRISPR-Cas9-sgRNAs technology for gene editing of the two orthologs napba and napbb. We observed that napb crispants (CR) show shorter motor neuron axons length together with altered locomotion behavior, including significant increases in larvae total distance traveled, swimming velocity, and rotation frequency, indicating that these behavioral changes effectively mimic the human epileptic phenotype. We applied microelectrode array (MEA) technology to monitor neural activity and hyperactivity in the zebrafish model. The napb CR shows hyperexcitability in the brain region. By combining behavioral tests with electrophysiological MEA assays, the established NAPB zebrafish model can be employed to study the pathophysiological mechanisms of ASD and epilepsy to screen potential therapeutic drugs. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-025-96862-2